Early Ventilation-Heart Rate Breakpoint during Incremental Cycling Exercise - Gravier, G.; Delliaux, S.; Ba, A.; Delpierre, S.; Guieu, R.; Jammes, Y. (International Journal of Sports Medicine, 2014)
Previous observations having reported a transient hypoxia at the onset of incremental exercise, we investigated the existence of concomitant ventilatory and heart rate (HR) breakpoints.33 subjects executed a maximal cycling exercise with averaging for successive 5-s periods of HR, ventilation, tidal volume (VT), mean inspiratory flow rate (VT/Ti), and end-tidal partial pressures of O2 (PETO2) and CO2. In 10 subjects, the transcutaneous partial pressure of O2 (PtcO2) was recorded and the venous blood lactic acid (LA) concentration measured.At the beginning of exercise, PETO2 decreased, reaching a nadir, then progressively increased until the exercise ended. PtcO2 varied in parallel. Whether or not a 0-W cycling period preceded the incremental exercise, the rate of changes in VE, VT, VT/Ti and HR significantly increased when the nadir PO2 was reached. The ventilatory/ HR breakpoint was measured at 33±4% of VO2max, whereas the ventilatory threshold (VTh) was detected at 67±4% of VO2max and LA began to increase at 45 to 50% of VO2max.During incremental cycling exercise, we identified the existence of HR and ventilatory breakpoints in advance of both lactate and ventilatory thresholds which coincided with modest hypoxia and hypercapnia.
Keywords: incremental cycling; hypoxemia; ventilatory breakpoints; heart rate breakpoint; breathing pattern